(untitled) (Stavební obzor - Civil Engineering Journal, 2019)
This article deals with parametric modelling of three types of windows from the 19th and 20th century. All three types of windows are fitted in the same set of buildings – a coaching inn. The article describes the design and creation process of library for Historic Building Information Modelling (HBIM). The design and development of the window-library are based on the analyses of available metric survey documentation - photo documentation, point cloud, drawings of ground plan. The characteristics of the final Building Information Model (BIModel) are derived from the nature of the case study, respectively type of historical building, Level of Details (LoD) of surveys, purpose of modelling and required Level of Development (LOD). Based on these specifications, it is possible to realize three different types of BIModel - simplified, detailed and shape-faithful. The aim of this modelling was to design a library usable for detailed BIModel.